2010
DOI: 10.1111/j.1742-6723.2009.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis and clinical application of the working dimensions of cricothyroid membrane in south Indian adults: With special relevance to surgical cricothyroidotomy

Abstract: Working dimensions are smaller in the Indian group compared with western publications. Endotracheal tubes ranging from size 3.0 to 6.0 might be used for cricothyroidotomy in the adult south Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…15,16 Characteristics and anatomic measurements of the subjects were as follows: Subject 1, non-obese female with a small neck circumference; Subject 2, morbidly obese female with a large neck circumference and significant pre-tracheal subcutaneous tissue; Subject 3, tall female with a small neck circumference; and Subject 4, non-obese female with the lowest TMD/SMD ratio of the four subjects. Subjects were positioned in a standardized fashion with the neck optimally extended (as the height of the CTM increases upon neck extension, 20 exposing a larger working area to perform a cricothyrotomy. Table 2 represents participant characteristics of the anesthesia providers and surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Characteristics and anatomic measurements of the subjects were as follows: Subject 1, non-obese female with a small neck circumference; Subject 2, morbidly obese female with a large neck circumference and significant pre-tracheal subcutaneous tissue; Subject 3, tall female with a small neck circumference; and Subject 4, non-obese female with the lowest TMD/SMD ratio of the four subjects. Subjects were positioned in a standardized fashion with the neck optimally extended (as the height of the CTM increases upon neck extension, 20 exposing a larger working area to perform a cricothyrotomy. Table 2 represents participant characteristics of the anesthesia providers and surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…Cadaver studies that examined location and movement of the cricothyroid membrane have been published [6][7][8][9] but a PubMed search using key words 'identification' and 'cricothyroid membrane' for the time period 1999-2017 did not identify any studies that assessed the location of the CTM with change in head and neck position in living people, nor any studies which indicated that change in position of head and neck had any effect on the height of the CTM. We were, therefore, unable to perform an a priori power analysis to determine an appropriate sample size to evaluate our two hypotheses using tests of statistical significance, so we designed an observational pilot study to help us decide whether our hypotheses were worthy of further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of the study was to assess whether a Previous ultrasound studies of the CTM in cadavers [8,9] used 23, 24 or 25 cadavers per group and showed good homogeneity within groups, so we planned to recruit 25 volunteers for our study. (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The size of the cricothyroid membrane in the western population is reported as 7.5 mm–10.5 mm in female cadavers and 10.0 mm–13.0 mm in male cadavers . A study examining the south Indian population found the cricothyroid membrane to be much smaller, at 3.0 mm–8.4 mm in female and 3.0 mm–10.0 mm in male cadavers . The same study reported that the height of the cricothyroid membrane should be used to judge appropriate tracheal tube size for emergency cricothyotomy; the external diameter of the tracheal tube should be smaller than the height of the cricothyroid membrane measured in the neutral position.…”
Section: Introductionmentioning
confidence: 99%